Atranones with enhancement neurite outgrowth capacities from the crinoid-derived fungus stachybotrys chartarum 952. Issue 52 (28th December 2017) - Li, Yong-Fang; Zhang, Pan-Pan; Yan, Su-Jun; Xu, Jia-Yi; Niaz, Shah-Iram; Chand, Raza; Eddie Ma, Chi Him; Lin, Yong-Cheng; Li, Jing; Liu, Lan
Abstract: Seven new atranones (1–5, 7, 10 ) and three known analogues (6, 8, 9 ) were isolated from the marine crinoid-derived toxigenic fungus Stachybotrys chartarum 952. The structures of these compounds were elucidated by spectroscopic analysis as well as X-ray crystallographic analysis and electronic circular dichroism calculations. The absolute configurations of three known compounds6, 8, 9 were first determined. Compound8 promoted neurite outgrowth from adult DRG neurons significantly without affecting cell survival at 1  μ g/mL concentrations. Graphical abstract: Highlights: Seven new atranones were isolated from the marine crinoid-derived toxigenic fungus Stachybotrys chartarum 952. The absolute configurations of methylatranone B, atranone B, and methylatranone A, were first identified. Atranone B promoted neurite outgrowth from adult DRG neurons significantly without affecting cell survival.